John Ellis Wool papers - Wool, John Ellis, 1784-1869.
ALS (1836 November 21; Headquarters, Army of the Cherokee Nation, New Echota, Ga.) from Wool to Mrs. N. Warren relating chiefly to Wool's service as commander of the U.S. Army of the Cherokee and to the Cherokee Indians; ALS and typewritten transcript of the letter (1865 August 2; Troy, [N.Y.]) from Wool to Benson J. Lossing discussing James Buchanan, Abraham Lincoln, Winfield Scott, William Henry Seward, and the abolition of slavery; letter with holograph note (1866 May 15; Troy, [N.Y.]) from Wool to De B. Randolph Keim regarding the service of Thomas Beverly Randolph in the War of 1812 and the Mexican-American War; note (1901) signed by Keim pertaining to the 1866 letter; and ALS (? October 7; Troy, [N.Y.]) from Wool concerning Lewis Cass and the presidential election of 1852. Includes a print of a painting of Wool.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Buchanan, James, -- 1791-1868.; Cass, Lewis, -- 1782-1866.; Keim, De B. Randolph -- 1841-1914 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lossing, Benson John, -- 1813-1891 -- Correspondence; Randolph, Thomas Beverly, -- 1793-1867.; Scott, Winfield, -- 1786-1866.; Seward, William Henry, -- 1801-1872.; United States. -- Army of the Cherokee; Cherokee Indians; Cherokee Indians -- Government relations; Mexican War, 1846-1848.; Presidents -- United States -- Election -- 1852.; Slavery -- United States; United States -- History -- War of 1812.; United States -- Politics and government -- 1775-1783.; Army officers